VARIASI MORFOLOGI SISIK PADA IKAN FAMILI CYNOGLOSSIDAE: SEBUAH TINJAUAN LITERATUR - Suchy Rahmadhani; Abdul Razak (Jurnal Biogenerasi, 2026)
The tonguefish (family Cynoglossidae) is characterized by its flattened body and is widely distributed across the Indo-Pacific, India, Pakistan, and the Red Sea. This study aims to analyze the variation of scale types in the family Cynoglossidae based on a literature review. The literature search was conducted using electronic databases, namely Google Scholar, PubMed, and ScienceDirect. The keywords used in the search were "Cynoglossidae", "scale morphology", "tonguefish", and "scales". A total of 9 articles met the inclusion criteria and were extracted for data. Fifteen species of tonguefish were successfully identified in terms of their scale types. Three patterns of scale variation were found: ctenoid scales on both sides, ctenoid scales on the eyed side and cycloid scales on the blind side, and cycloid scales on both sides. The conclusion of this review is that the scale types in the family Cynoglossidae vary among species and show consistent patterns, thus they can serve as supporting characters in taxonomic identification and classification.